(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
in this article, the role, importance, tasks and characteristics of the accompanist in the performance of folk instruments, the restoration of national spiritual values in the years of independence, the full-fledged professional activity of the accompanist, memory, in unexpected situations-the presentation of a set of psychological personal qualities such as reaction and resourcefulness, endurance and will, pedagogical tact and sensitivity, and its importance in the general ensemble is highlighted. The main skills used in the performance are intuitive perception of the soloist, rich artistic taste, deep understanding of the content of the musical work, and preservation of "individuality", which is extremely valuable.